A Cheek Nodule in a Child: Be Aware of Idiopathic Facial Aseptic Granuloma and Its Differential Diagnosis - Miconi, Francesco (Int J Environ Res Public Health, 2019)
Background: Idiopathic facial aseptic granuloma (IFAG) is a rare skin disease that typically presents in children with one or more nontender, erythematous to violaceous nodules located on the cheeks or eyelids. Lesions are not accompanied by other skin abnormalities. IFAG remains a diagnostic challenge in pediatric dermatology, because several diseases may present with similar signs. Case presentation: A three-year-old girl with a previous negative clinical history was referred to our hospital for the evaluation of some asymptomatic nodules on the convexity of the left cheek. The nodules had appeared two months before, and had gradually increased in size. Her mother denied any association with trauma or insect bites. The nodules had a hard-elastic consistency, were moderately firm, and were not fluctuant. No associated lymphadenopathy was observed. The girl was afebrile and in good general condition. A histologic evaluation of a biopsy specimen revealed an inflammatory, granulomatous-diffuse infiltrate in the superficial and deep dermis consisting of giant cells, histiocytes, lymphocytes, neutrophils, eosinophils, and plasma cells. The Ziehl–Neelsen stains, Gram-stains, and cultures were negative. Suspecting an IFAG, treatment with topical fusidic acid and oral clarithromycin for 14 days was started. After two months, the lesion resolved and did not recur. Conclusion: This case shows how to differentiate IFAG from other dermatologic diseases associated with a negative evolution. Treatment with oral clarithromycin was effective in our patient. However, more scientific evidence is needed to evaluate the most suitable antibiotic therapy. Further studies are also needed to establish whether antibiotics actually impact IFAG prognosis.